2020
DOI: 10.3390/ijms21020434
|View full text |Cite
|
Sign up to set email alerts
|

The EGFR-ERK/JNK-CCL20 Pathway in Scratched Keratinocytes May Underpin Koebnerization in Psoriasis Patients

Abstract: Epidermal keratinocytes represent a rich source of C-C motif chemokine 20 (CCL20) and recruit CCR6+ interleukin (IL)-17A–producing T cells that are known to be pathogenic for psoriasis. A previous study revealed that scratch injury on keratinocytes upregulates CCL20 production, which is implicated in the Koebner phenomenon characteristically seen in psoriasis patients. However, the molecular mechanisms leading to scratch-induced CCL20 production remain elusive. In this study, we demonstrate that scratch injury… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 61 publications
0
17
0
Order By: Relevance
“…Other studies also underpin a possibility that IL-17A activates EGFR [98,181,182]. Chen et al have demonstrated that IL-17A transactivates EGFR in keratinocyte stem cells [98].…”
Section: Il-17a and Keratinocyte Proliferation/differentiationmentioning
confidence: 97%
See 1 more Smart Citation
“…Other studies also underpin a possibility that IL-17A activates EGFR [98,181,182]. Chen et al have demonstrated that IL-17A transactivates EGFR in keratinocyte stem cells [98].…”
Section: Il-17a and Keratinocyte Proliferation/differentiationmentioning
confidence: 97%
“…Although dermal dendritic cells and T cells express CCL20 in the psoriatic dermis [159], the expression of CCL20 is largely confined to the psoriatic epidermis, suggesting that epidermal keratinocytes are the major source of CCL20 production in psoriatic lesions [158,159]. CCL20 is constitutively expressed in cultured keratinocytes [201,204], and its production is upregulated by TNF-α and IL-17A [182,204]. Scratch injury upregulates the gene expression of CCL20, CXCL8, and IL36G, which may be related to the scratch-induced Koebner phenomenon frequently observed in patients with psoriasis [201].…”
Section: Il-17a and Cyto/chemokines In Keratinocytesmentioning
confidence: 99%
“…15,25,60 Scratch-induced CCL20 upregulation is mediated by activation of epidermal growth factor receptor, extracellular signal-related kinase and partly by c-Jun N-terminal kinase. 26 These scratch injury-mediated reactions are very beneficial for physiological, coordinated wound healing in healthy individuals, because CXCL8, CCL20 and IL-17A accelerate epithelial wound healing. [64][65][66][67] In addition, neutrophils are the first immune cells to infiltrate wounded sites, and appropriate neutrophilic recruitment is critical for efficient wound healing ( Fig.…”
Section: Psoriasis and Scratch Injurymentioning
confidence: 99%
“…2). 15,26,75,76 IL-17A directly stimulates keratinocyte proliferation (upregulation of Ki-67 and keratin 16), and induces abnormal keratinocyte differentiation by affecting the expression of transglutaminase 1, filaggrin and involucrin ( Fig. 2).…”
Section: Psoriasis and Scratch Injurymentioning
confidence: 99%
See 1 more Smart Citation